Regular Open-Skill Exercise Generally Enhances Attentional Resources Related to Perceptual Processing in Young Males - Zhou, Fangyuan; Xi, Xuan; Qin, Chaoling (Frontiers in Psychology, 2020)
This study aimed to examine whether the regular open-skill exercise led to a selective improvement or a general improvement on cognitive function in healthy young males. Besides, we also intend to expand previous studies by looking into the temporal dynamics of early information processes and cognitive processes through appraising the extensive temporal series of stimulus-locked ERP components. Sixty healthy young males were classified into two groups: those who regularly participated in the open-skill exercise for at least 2 years (n=30), and those who exercised rarely. The participants conducted the Stroop task with event-related brain potential (ERP) recorded. The results indicated that compared with the rare exercise group, the open-skill exercise group led to a selective improvement for accuracy under the incongruent condition. And the open-skill exercise group also led to a selective improvement for response time under the incongruent condition. Moreover, the open-skill exercise group yielded larger P200 amplitudes under both the congruent and incongruent conditions compared with the rare exercise group. The findings suggest that the regular open-skill exercise may promote executive function by an increase in the allocation of attentional resources related to perceptual processing and greater interference control during cognitively demanding tasks in healthy young males.